2016
DOI: 10.1186/s12888-016-0950-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of benign paroxysmal positional vertigo in patients with anxiety disorders: a nationwide population-based retrospective cohort study

Abstract: BackgroundThe objective of this study was to evaluate the risk of benign peripheral persistent vertigo (BPPV) among patients with anxiety disorders by using the Taiwan National Health Insurance Research Database (NHIRD).MethodsWe conducted a retrospective study of 15,470 participants (7735 anxiety disorder patients and 7735 control patients) selected from the NHIRD. Patients were observed for a maximum of 9 years to determine the rates of newly diagnosed BPPV. A Cox regression model was used to evaluate the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
3
25
1
2
Order By: Relevance
“…The median age of the patients in our series is similar to that observed in other studies at specialised clinics [16] [30] and primary care practices [23]. [37]. No signi cant differences between men and women were found in terms of response to the EM during follow-up, even though baseline DHI-S scores were higher among women.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The median age of the patients in our series is similar to that observed in other studies at specialised clinics [16] [30] and primary care practices [23]. [37]. No signi cant differences between men and women were found in terms of response to the EM during follow-up, even though baseline DHI-S scores were higher among women.…”
Section: Discussionsupporting
confidence: 86%
“…It is not uncommon for patients with BPPV to experience psychiatric-psychosomatic disorders such as depression or anxiety [38]. Anxiety disorders, in fact, have been found to be 2.17 times (95% CI, 1.63-2.90, P < 0.001) more common in patients with BPPV than in controls following adjustment for age, sex, and comorbidities [37].…”
Section: Discussionmentioning
confidence: 99%
“…The general symptoms defined in ICD‐9‐CM include hallucinations, dizziness and giddiness, sleep disturbances, and so on, which are the common symptoms and complaints about delusional and anxiety disorders patients according to DSM‐5 . About 17% of the patients in delusional disorders present hallucinations; anxiety disorders patients were more likely to develop vertigo than the control patients . Among patients with anxiety disorders, the confidence of simultaneous general symptoms and sleep disturbances was high (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…37 These may be possibly due to the side effects for gastrointestinal diseases of antipsychotic medicine 38 About 17% of the patients in delusional disorders present hallucinations 40 ; anxiety disorders patients were more likely to develop vertigo than the control patients. 41 Among patients with anxiety disorders, the confidence of simultaneous general symptoms and sleep disturbances was high (Figure 1). According to the previous study, sleep disturbances were bidirectionally related to anxiety; the relationship was found where anxiety predicted excessive daytime sleepiness.…”
Section: Number Of Patients With and Number Of Patients Withmentioning
confidence: 99%
“…Psychiatric disorders or emotional stress are frequently observed in patients suffering from vertigo 12 13. The results of most studies have been reported the higher rate of coexistence of depression and vestibular disorders,14–16 which may lead to a vicious circle and a serious influence on the quality of life 17. Peripheral vertigo may play an essential role in the pathophysiology of development of subsequent depressive disorder.…”
Section: Introductionmentioning
confidence: 99%